Exploring how cognitive-behavioral physical activity links ruminative thinking and mental wellbeing in sports high school adolescents - Derelioğlu, Mehmet; Vural, Mustafa; Çimen, Erkan; Saki, Ünal; Yağız Saraçoğlu, Yusuf; Karataş, Baykal; Saç, Ajlan; Yamaner, Emre; Halmatov, Medera; Yılmaz, Coşkun; Öztaş, Mehmet; Arıkan, Gökhan; et al. (Frontiers in Psychology, 2025)
IntroductionThis study examined the associations among ruminative thinking style (RTS), subjective wellbeing (SWB), and cognitive-behavioral physical activity (CBPA) in a sample of 1,326 adolescents (aged 14–18) from sports high schools.MethodUsing validated self-report measures, data were analyzed through bootstrapped mediation models.ResultsRTS was negatively associated with SWB (β = −0.1792, p < 0.001), while CBPA showed a partial mediating effect in this relationship (indirect β = 0.0779, p < 0.001).DiscussionThese results suggest that cognitive-behavioral orientations toward physical activity may buffer the negative impact of rumination on wellbeing. Consistent with cognitive-behavioral therapy (CBT) principles, CBPA could provide adolescents with self-regulatory strategies that support mental health. However, the cross-sectional and self-report design, as well as the focus on sports high school students, limit causal inference and generalizability. Future longitudinal and cross-cultural studies are needed to confirm these findings. Overall, the study provides preliminary evidence that CBPA-informed approaches may hold promise for promoting adolescents' mental wellbeing.